BTEX Exposure Assessment and Inhalation Health Risks to Traffic Policemen in the Klang Valley Region, Malaysia - Noor Fatihah Mohamad Fandi; Juliana Jalaludin; Mohd Talib Latif; Haris Hafizal Abd Hamid; Mohd Fairus Awang (Aerosol and Air Quality Research)
Abstract Benzene, toluene, ethylbenzene, m,p-xylene, and o-xylene (collectively referred to as BTEX), which are prevalent in the ambient air of urban environments, potentially cause chronic health effects, particularly among outdoor workers. Aim of this study was to evaluate BTEX concentrations in the Klang Valley of Malaysia and assess the health risks to urban traffic police officers, whose duties include controlling the traffic flow and enforcing traffic laws. Air samples were collected with low-flow personal samplers during the officers’ work shifts outdoors, and the BTEX content was then analyzed via gas chromatography-mass spectrometry (GC-MS) coupled with thermal desorption (TD). A probabilistic method based on Monte Carlo simulation was applied to determine the cancer risk (CR) and hazard quotient (HQ), and a sensitivity analysis was performed to identify the greatest contributors to the estimated risks. The total BTEX concentration in the samples averaged 211.83 µg m–3, with the largest component being toluene (averaging 89.08 µg m–3 in concentration), followed by m,p-xylene (37.25 µg m–3), o-xylene (35.80 µg m–3), benzene (25.82 µg m–3), and ethylbenzene (23.89 µg m–3). The average CR value for benzene (5.31 × 10–6) as well as the 95th percentiles of the CR values for benzene and ethylbenzene (1.70 × 10–5 and 2.12 × 10–6, respectively) exceeded the acceptable level of exposure (1.0 × 10–6). The HQ values for all of the BTEX species were less than one. The sensitivity analysis revealed that the most influential parameter in increasing the estimated CR and HQ was the exposure duration, followed by the BTEX concentration. The estimated CR indicates that the prolonged exposure to benzene and ethylbenzene experienced by traffic police officers exacerbates the risk of adverse health effects. These results, which provide baseline data for determining the occupational risk to individuals who are exposed to BTEX while working on or near a road, emphasize the need for additional regulations, including the use of appropriate respiratory protective equipment.